Оптимизация огнезащитно-огнетушащих свойств состава для предотвращения и локализации пожаров в природном комплексе методом математического планирования эксперимента - Bogdanova Валентина; Kobets О.; Lyudko Александр; Kirlitsa В. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2012)
With the help of mathematical planning of experiments, we has determined the optimal ratio of the main components developed fire-retardant-extinguishing composition (FREC) to prevent and extinguish forest and peat fires in natural complex. It has been established that the efficiency of FREC rises with increasing the quantity of reagents containing phosphorus and nitrogen and/or metal and nitrogen in the formulation of the composition. The absolute values of regression coefficients indicate that the greatest influence on extinguishing efficiency has nitrogen containing in the FREC recipe.